2022
DOI: 10.1177/13674935211059980
|View full text |Cite
|
Sign up to set email alerts
|

The indirect health impacts of the COVID-19 pandemic on children and adolescents: A review

Abstract: It is pertinent to examine potentially detrimental impacts of the coronavirus disease 2019 (COVID-19) pandemic on young people. We conducted a review to assess the health impacts of the COVID-19 pandemic on children and adolescents. Databases of MEDLINE, Embase and the Cochrane Library were searched in June 2020, using keywords for ‘children’, ‘adolescents’ and ‘COVID-19’. English papers discussing young people in context to the COVID-19 pandemic were included. Quality of selected studies was evaluated and sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
1
11
0
2
Order By: Relevance
“…Several reviews and studies have examined the short and long-term effects of the COVID-19 pandemic on the mental health of young people [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Bussières et al [ 52 ] found that mental health problems in children up to 13 years of age increased three times more in European countries than in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews and studies have examined the short and long-term effects of the COVID-19 pandemic on the mental health of young people [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Bussières et al [ 52 ] found that mental health problems in children up to 13 years of age increased three times more in European countries than in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Europe was not prepared for the most recent crises, particularly regarding protection and support of younger populations. The negative health consequences have been amply documented for the COVID-19 crisis [ 3 , 4 ] while other crises are less well investigated. For a prepared and sustainable society, public health decision-making processes are needed that 1) are more inclusive to any vulnerable group, such as children and adolescents, 2) systematize in a transparent way the best available knowledge from all disciplines on all consequences (i.e., effects and side effects; short and long-term impacts) of potential public health decisions, 3) consult the younger populations (and guardians) as any other stakeholder and, 4) provide public services that protect fundamental rights of children and youth, e.g., safety from violence, having a home and minimal financial support, remain available in times of crises and anticipate emerging needs.…”
Section: Action 1: Increase Preparedness To Ensure Children’s Health ...mentioning
confidence: 99%
“…Crises disproportionately affect the most vulnerable, and risk to further decrease the resilience of young people, their families and communities [ 3 , 4 ]. To address the preparedness for future crises and the most pressing public health problems for children and adolescents, the European Public Health Association (EUPHA) Child and Adolescent Public Health Section proposes the following actions to counteract the adverse health consequences of crises and to promote healthy environments, health and resilience among children and adolescents.…”
mentioning
confidence: 99%
“…Hal tersebut berdampak pada kesehatan mental, meningkatkan risiko paparan kekerasan dalam kondisi lockdown, dan pada remaja meningkatkan risiko HIV dan kehamilan dini (UNICEF, WHO, PMNCH, & UHC2023, 2021). Masalah kesehatan mental yang ditemukan dalam masa pandemi yaitu, meningkatnya episode depresif, afek negatif, ketegangan, ketakutan dan kesepian (Branje & Morris, 2021;Oostrom, et al, 2019;Theberath et al, 2022;Wang et al, 2021). Masalah kesehatan lain yang ditemukan yaitu terhambatnya pelayanan pencegahan dan pengobatan Penyakit Tidak Menular (PTM); menurunnya angka vaksinasi; masalah nutrisi, penurunan aktivitas fisik (León & Arguello, 2021;Oostrom et al, 2019;PMNCH, 2021;Zemrani et al, 2021).…”
Section: Pendahuluanunclassified
“…Masalah kesehatan mental yang ditemukan dalam masa pandemi yaitu, meningkatnya episode depresif, afek negatif, ketegangan, ketakutan dan kesepian (Branje & Morris, 2021;Oostrom, et al, 2019;Theberath et al, 2022;Wang et al, 2021). Masalah kesehatan lain yang ditemukan yaitu terhambatnya pelayanan pencegahan dan pengobatan Penyakit Tidak Menular (PTM); menurunnya angka vaksinasi; masalah nutrisi, penurunan aktivitas fisik (León & Arguello, 2021;Oostrom et al, 2019;PMNCH, 2021;Zemrani et al, 2021). Tidak hanya itu, pandemi COVID-19 juga menyebabkan penurunan penyesuaian akademik pada pelajar (Branje & Morris, 2021).…”
Section: Pendahuluanunclassified